Dye based photodiodes for solar energy applications - Mensah-Darkwa, K.; Ocaya, R.; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Soylu, M.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2017)
Coumarin (CO) doped methylene blue (MB) organic photo-devices were fabricated. The CO-doped MB (0.00, 0.01, 0.03, 0.05, 0.1 wt% CO) were coated onto the surface of a p-type Si substrate by drop casting method. Some electrical parameters of the devices have been examined by current-voltage (I-V), capacitance-voltage (C-V), and conductance-voltage (G-V) measurements. The fabricated devices had excellent rectifying properties. The diode exhibits a non-ideal diode behavior due to the series resistance and interface layer. The ideality factor, the barrier height, and the series resistance values of the diode as a function of doping and light illumination have been estimated using modified Cheung-Cheung and Norde's method. The highest I-photo/I-dark photosensitivity of 5606 was observed for the diode having 0.01 CO doping at 100 mW/cm(2) under -3 V. Furthermore, change of capacitance and conductance measurements with frequency is related to the existence of interface states. A maximum power conversion efficiency of 2.4% is estimated for the fabricated devices. The results reveal that coumarin-doped methylene blue/p-Si heterojunction can be used as a photodiode in optoelectronic applications. It is also usable in low-power photovoltaic applications.
Keywords: Electrical-Properties; Methylene-Blue; Temperature; Diodes; Cells; Films; Si